2016
DOI: 10.1007/s00428-016-2044-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mutations in the BRAF gene in patients with KIT and PDGFRA wild-type gastrointestinal stromal tumors

Abstract: Gastrointestinal stromal tumors (GISTs) are characterized by mutations in exons 9, 11, 13, and 17 of KIT or exons 12, 14, and 18 of PDGFRA gene. However, approximately 10 to 15 % of GISTs lack the mutations in KIT and PDGFRA, and these are referred to as wild-type GISTs which are less sensitive to tyrosine-kinase inhibitors. The aim of this study was to detect BRAF mutations in patients with wild-type GISTs. We applied a sensitive allele-specific PCR, which was optimized using the V600E mutation-harboring cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
1
23
1
Order By: Relevance
“…In contrast Shitara et al found no mutations in RAC1, PPP6C, STK19 genes in melanomas associated with intermittent sun-exposed melanomas [23]. Further, our results indicate that allele-specific PCR is more sensitive than Sanger sequencing [19,24], so we used allele-specific PCR to detect BRAF V600E mutation. We performed allele-specific PCR only on BRAF, because it had already been applied by Jasek et al [19].…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In contrast Shitara et al found no mutations in RAC1, PPP6C, STK19 genes in melanomas associated with intermittent sun-exposed melanomas [23]. Further, our results indicate that allele-specific PCR is more sensitive than Sanger sequencing [19,24], so we used allele-specific PCR to detect BRAF V600E mutation. We performed allele-specific PCR only on BRAF, because it had already been applied by Jasek et al [19].…”
Section: Discussioncontrasting
confidence: 61%
“…We used allele-specific PCR for confirmation of V600E mutation in the BRAF gene. This assay was previously established in our laboratory and the allele-specific PCR for the BRAF V600E mutation was adopted from Jasek et al [19].…”
Section: Methodsmentioning
confidence: 99%
“…The subgroup of the remaining KIT/PDGFRA WT GIST, but not SDH- deficient , have been further characterized: 4–13% carry a BRAF V600E mutation, are localized more frequently in small intestine and seem to have a more favourable prognosis [1821]. Within the not SDH- deficient , some GIST have a neurofibromatosis (NF) type 1 mutation and show a female prevalence, a frequent non-gastric site and multifocal localization often unveiling an unrecognized NF1 syndromic condition [2226].…”
mentioning
confidence: 99%
“…Following reported thermal conditions and primer pairs [28], BRAF gene was only sequenced for 22 GISTs retaining the wild-type KIT and PDGFRA genes, given that the concurrence of BRAF mutation with either KIT or PDGFRA mutation is extraordinary rare, if any, in GISTs [29, 30]. In fact, all these 22 cases revealed no mutation in the hotspot exon 15 that encompasses codon Val600 (Supplementary Figure 1A).…”
Section: Methodsmentioning
confidence: 99%